Shadowed summer - Mitchell, Saundra (Delacorte Press, 2009)
In the small town of Ondine, Louisiana, fourteen-year-old Iris uncovers family secrets when she conjures up the ghost of a boy missing for decades and decides to solve the mystery of his disappearance.